Perceived self-efficacy gains following an interprofessional faculty development programme in geriatrics education. Issue 4 (3rd July 2016) - Coogle, Constance L.; Hackett, Lewis; Owens, Myra G.; Ansello, Edward F.; Mathews, Jennifer H.
ABSTRACT: This study was designed to document outcomes of a 10-month, 160-hour interprofessional faculty development programme in geriatrics. The programme was structured around a series of collaborative competencies in older adult care established. Six domains covering 23 competencies were used to create an evaluation instrument designed to measure changes in self-efficacy as a result of the training programme. These competencies are covered through a series of interactive and didactic seminars offered on a monthly basis throughout the academic year. Twenty-six faculty participants indicated their levels of perceived self-efficacy with respect to each partnership for health in aging competency before and after the training. Statistically significant results were found with respect to every competency in each domain. Prior to the training self-efficacy levels were lower than the mean ratings collected 10 months later when the training concluded. The largest perceived self-efficacy gains were seen in the "evaluation and assessment", "care planning and coordination across the care spectrum", and "healthcare systems and benefits" domains. These may reflect areas that were not covered extensively during the participants' previous healthcare-related training. Overall, the data demonstrate how a carefully constructed interprofessional faculty development programme can successfully engender confidence in geriatric competencies across multiple professions.